2012
DOI: 10.1186/1471-230x-12-70
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the temporary placement of 3 different self-expanding stents for the treatment of refractory benign esophageal strictures: a prospective multicentre study

Abstract: BackgroundRefractory benign esophageal strictures (RBESs) have been treated with the temporary placement of different self-expanding stents with conflicting results. We compared the clinical effectiveness of 3 types of stents: self-expanding plastic stents (SEPSs), biodegradable stents, and fully covered self-expanding metal stents (FCSEMSs), for the treatment of RBES.MethodsThis study prospectively evaluated 3 groups of 30 consecutive patients with RBESs who underwent temporary placement of either SEPSs (12 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 31 publications
(143 reference statements)
3
49
0
Order By: Relevance
“…Therefore, elective removal of the stent within four weeks of placement was recommended. Three studies [10,14,15] has been published showing the outcome of Ella esophageal BD stent since it became available to use in 2007, all these studies showed technical success rate of 100%, clinical success rate 30% [14] -100% [10,15] and migration rate 9% [10] -20% [14].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, elective removal of the stent within four weeks of placement was recommended. Three studies [10,14,15] has been published showing the outcome of Ella esophageal BD stent since it became available to use in 2007, all these studies showed technical success rate of 100%, clinical success rate 30% [14] -100% [10,15] and migration rate 9% [10] -20% [14].…”
Section: Discussionmentioning
confidence: 99%
“…Post-operative length of stay was a median of 1 (range 1 to 5) d following successful colonoscopic resection, and uncomplicated except for post-polypectomy syndrome and urinary retention in two patients. Amongst patients requiring surgical resection, length of stay was longer (median 5.5 [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] d, p = 0.001, Mann Whitney), with four patients suffering from complications (anastomotic leak, an intra-abdominal fluid collection managed conservatively, urinary retention, and sepsis without identified source, respectively). Conclusions: LACE is an effective strategy, enabling safe and complete polypectomy for lesions that are difficult to access or resect at primary colonoscopy in about half of carefully selected patients.…”
Section: Discussionmentioning
confidence: 99%
“…ClinicalTrials.gov NCT01368289. Gastroenterology and Hepatology, Epworth Hospital, Melbourne, Victoria, Australia,5 Department of Gastroenterology and Hepatology, Lyell McEwin Hospital, Adelaide, South Australia, Australia,6 Department of Gastroenterology and Hepatology, Sir Charles Gairdner Hospital, Perth, Western Australia, Australia,7 Department of Gastroenterology and Hepatology, Western Hospital, Melbourne, Victoria, Australia, 8 The Queensland Institute of Medical Research, Brisbane, Australia, Envoi Specialist Pathologists, Brisbane, Australia, 9 Institute of Clinical Pathology and Medical Research, Westmead Hospital, Sydney, New South Wales, Australia Background and aims: Traditional serrated adenomas (TSAs) are part of the group of serrated colorectal polyps and represent 1.5% of all colorectal lesions. Serrated polyps ≥1 cm are associated with synchronous colorectal carcinoma.…”
mentioning
confidence: 99%
“…Success rates of these treatments are 80-90%, but 30-60% of patients develop dysphagia in long term follow-up and needs dilatation again. Recurrence rate is higher in complex strictures and with the increased number of sessions complication rate will also be higher 4,8 . There are three types of dilatators: Mercuryweighted bougies (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Endoscopic dilatation is the basic treatment option and SGD is the choice of treatment. SGD may be performed with or without fluoroscopy 1,3,4 . 80-90% of patients can be treated by SGD or balloon dilatation but these may be insufficient may recur in some of the patients.…”
Section: Introductionmentioning
confidence: 99%